Dyeing of Silk with Anthocyanins Dyes Extract from Liriope platyphylla Fruits. (19th August 2014) - Wang, Huayin; Li, Ping; Zhou, Wenlong
Abstract : A new source of natural anthocyanins dyes, from Liriope platyphylla fruit, is proposed. This paper analyzes the dye extracts, the primary color components of the extracts, the color features of the extracts under different pH conditions, and their application in silk dyeing. The research shows that, nine anthocyanins are found in   L. platyphylla fruits by analyzing the results of the HPLC/DAD, MS, and MS/MS spectra. The five major anthocyanins related to delphinidin, petunidin, and malvidin derivatives take up 91.72% of total anthocyanin contents. The color of the solution is red under acidic condition (pH < 3.0) and stays in yellow under alkaline condition with pH values above 7.0. The dye extracts applied to silk fabric with mordant free dyeing show different color under different pH conditions, changing between purple, blue, green, and yellow. However, the dyed colors is light and the dyeing rate is low. Metal mordant such as Sn in chelation enhances the dye depth and improves the fastness of the dyed silk fabrics, especially in silk fabrics dyed by premordanting and metamordanting.